x+4=6(y-1)

Simple and best practice solution for x+4=6(y-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+4=6(y-1) equation:


Simplifying
x + 4 = 6(y + -1)

Reorder the terms:
4 + x = 6(y + -1)

Reorder the terms:
4 + x = 6(-1 + y)
4 + x = (-1 * 6 + y * 6)
4 + x = (-6 + 6y)

Solving
4 + x = -6 + 6y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + x = -6 + -4 + 6y

Combine like terms: 4 + -4 = 0
0 + x = -6 + -4 + 6y
x = -6 + -4 + 6y

Combine like terms: -6 + -4 = -10
x = -10 + 6y

Simplifying
x = -10 + 6y

See similar equations:

| A+7A-A= | | 25+15x=235 | | (5X-135)= | | X+0.15x=83 | | 3x+2(6-x)+5=37-9x | | 30+15x=235 | | -6-9b=3-6b | | x/4+26=40 | | 23-4x=12+7x | | -2x+3(x+9)=17 | | -3r=-8r+10 | | 1x+2y=13 | | (x+4)(x-3)=(x-2)(x+1) | | 20y-4=18y+21 | | 35-5x=11+7 | | 20x-11-3x=9x+43 | | 132+10x=48+22x | | 3x+93-=360 | | 4(2c-3)+5(c-2)= | | 6x+12-4x-8=0 | | 5x+9y=27020 | | 2x+7+5=0 | | 12-5n=9+2n | | y[n]=x[n]-0.25y[n-2] | | 5-2x(x-3)=x(7-2x)+4 | | 6v+12=4v-8 | | 2(4y-5)=3y+15 | | 4(a+2)+3(a+3)= | | 8x-5=26 | | px+1=f | | 15s+9t=66 | | 3x+6=4-8x |

Equations solver categories